Modelling and assessing spatial big data: use cases of the OpenStreetMap full-history dump - Noskov, Alexey; Grinberger, A. Yair; Papapesios, Nikolaos; Rousell, Adam; Troilo, Rafael; Zipf, Alexander (Spatial planning in the big data revolution, 2019)
Many methods for intrinsic quality assessment of spatial data are based on the OpenStreetMap full-history dump. Typically, the high-level analysis is conducted; few approaches take into account the low-level properties of data files. In this chapter, a low-level data-type analysis is introduced. It...